Results From the German Fungal Keratitis Registry: Significant Differences Between Cases With and Without a History of Contact Lens Use. Issue 11 (15th November 2021) - Roth, Mathias; Holtmann, Christoph; Daas, Loay; Kakkassery, Vinodh; Kurzai, Oliver; Geerling, Gerd; Bäurle, Sebastian; Bayoudh, Wesal; Brücher, Viktoria; Cvetkova-Fischer, Nadezhda; Dias Blak, Matthias; Bornstein, Agnes; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: Fungal keratitis (FK) is a serious ophthalmic disease with a potentially devastating outcome that seems to be increasing in recent years. The use of contact lenses (CLs) was evaluated as a risk factor for FK to determine possible differences in course and outcome. Methods: Data from 173 cases reported in the German FK registry until August 2019 were evaluated regarding CL behavior, other ophthalmological and general risk factors, age, sex, identified pathogens, conservative and surgical therapy, visual acuity, and findings at admission and follow-up. Results: One hundred seventy-four eyes from 173 patients between 2000 and 2019 were included [64.4% women, median age 54 (39; 72) years]; 49.7% wore CL, of which 81.3% were soft CL, and 50.3% had no history of contact lens use (NCL). CL users were significantly more often women and otherwise healthy (CL: 80.2% vs. NCL: 48.9%; P < 0.0001). The spectrum of pathogens among CL users showed a significantly higher proportion of infections with filamentous pathogens, in particular Fusarium sp. (total filament: CL 69.8% vs. NCL 27.3%; P = 0.0001; Fusarium sp.: CL 50.0% vs. NCL 14.8%; P < 0.0001). Overall, 54.6% required keratoplasty and 8.6% enucleation. Conclusions: CLS are the most important risk factor for FK in Germany. With CLs, typically, the infection is caused by molds, and patients are comparably younger and otherwise healthy. Often, extensive surgery is needed. To evaluate changes in the pathogen and resistance spectrum and to further monitor possible CL-related risk factors, a consistent collection of data remains paramount.